A real interlocutor in elicitation techniques: does it matter? - Kanik, Mehmet (Research in Language, 2016)
This study investigates whether adding a real interlocutor to elicitation techniques would result in requests that are different from those gathered through versions with a hypothetical interlocutor. For this purpose, a written method is chosen. One group of 40 students receive a written discourse completion task (DCT) with two situations that ask respondents to write emails on paper to an imaginary professor. This data is compared to earlier data collected from 27 students, where a group of students composed emails for the same situations and sent them electronically to their professor. Thus, while one group write emails to a hypothetical professor, the other group is provided with a real interlocutor. The data is analyzed for the inclusion of opening and closing moves, density, the level of directness and the choices of moves in the opening and closing sequences, as well as the choices of supportive moves. Results indicate significant differences in (the) level of directness, and the choices of moves in the opening and closing sequences. The other analyses do not show significant differences. The findings reveal that the addition of a real interlocutor does make a difference, albeit not a drastic one. The results have implications for the design of elicitation techniques that aim to simulate real life.